Chapter 20 OPEC and Russia (2017)
Russia has long been a potential dream partner for the Organization of the Petroleum Exporting Countries (OPEC). Russia could greatly enhance the cartel’s market power and has several allies among the OPEC member states. During the 2010s, it seemed that the potential of the OPEC–Russia relationship was finally being realized as they grew closer. However, in this chapter we argue that the strengthened dialogue has little impact on physical oil output and the level of mutual commitment remains low. What they do share is an interest in the semblance of cooperation to push oil prices upward through impacting market psychology. This strategy is in line with the postmodern turn in Russian foreign policy, as proclaimed by Vladislav Surkov and others. It also has some important foreign policy side benefits for Russia, such as weakening its international isolation after the conflict in Ukraine and making it possible to simultaneously befriend various Middle Eastern countries that are at odds with each other. The OPEC–Russia dalliance is also convenient for a third party – the USA. Although the USA is still a net oil importer and its consumers dislike high oil prices, they benefit American oil companies and their employees and investors, especially in the shale oil sector. Arrangements between OPEC and Russia are thus not only a happy pro forma marriage, but also a successful ménage à trois.